VD_FINDINFO Jug / 2013 / 16 vom 26. Juli 2012 - VD Tribunal cantonal (2012)
PRÉSOMPTION D'INNOCENCE, IN DUBIO PRO REO, CONSTATATION DES FAITS, FIXATION DE LA PEINE, COMPLICITÉ | 25 CP, 47 CP, 10 CPP (CH)